THE EQUILIBRIUM GRAVEL COVERAGE OF THE DEFLATED GOBI ABOVE THE MOGAO GROTTOES OF DUNHUANG, CHINA - Wang W.; Dong Zh.; Wang T.; Zhang G. (My University, 2006)
Blown sand has caused considerable damage to the Dunhuang Mogao Grottoes of China. Controlling the blown sand requires a clear understanding of the processes that govern its production and movement. Experiments were conducted in a wind tunnel and in the field to define the relationships between sand production and gravel coverage in the gobi above the Mogao Grottoes. The gravel that covers the gobi’s surface controls wind erosion, irrespective of its shape and size. The equilibrium coverage by gravel over which no further sand is emitted due to wind erosion increases and the equilibration time that is taken to form the equilibrium gravel coverage decreases with increasing wind velocity. Gravel coverage has reached an equilibrium state in the portion of the gobi directly above the grottoes, but decreases towards the Mingsha Mountains. Drifting sand from these mountains is the main source of sand damage at the Mogao Grottoes. If no additional sand from the mountains were supplied to the gobi, gravel pavements would reach an equilibrium level of coverage and prevent further production of blowing sand. Sand blown from the gobi represents secondary reactivation of sediments originally produced in the Mingsha Mountains. Therefore, to control the blowing sand above the Mogao Grottoes, emphasis should be placed on controlling erosion from the Mingsha Mountains rather than local erosion of sand in the gobi.
Keywords: MOGAO GROTTOES OF CHINA; AEOLIAN SAND TRANSPORT; CONTROL OF BLOWN SAND; GRAVEL COVERAGE